Women’s Employment and Safety Perceptions : Evidence from Low-income Neighborhoods of Dhaka, Bangladesh - Ahmed, Tanima (World Bank, Washington, DC, 2021)
This brief uses the 2018 Dhaka Low-Income Area Gender, Inclusion, and Poverty (DIGNITY) survey to assess the gender gap in safety perceptions and analyze the correlation between women’s safety perception and their labor market outcomes. The analysis shows that women are significantly less likely than men to feel safe in the low-income neighborhoods of Dhaka. While the percentage of women who reported feeling safe increased with age, living standard, and the availability of streetlights, the percentage of women who reported feeling safe decreased with education and concern of eviction. The analysis further shows that this gender gap in safety perception disproportionately hurt women’s labor market outcomes. Women who feel safe are much more likely to be economically active, work outside their neighborhoods, and explore economic opportunities.